"Salón de actos del local social del comite regional en el casa de CNT/FAI. Portrait of A. Lorenzo on the wall. Copied from CNT collection. Series of 2 photos
"Salón de actos del local social del comite regional en el casa de CNT/FAI. Portrait of A. Lorenzo on the wall. Copied from CNT collection. Series of 2 photos.